Vascular Risk Factors and the Risk of Parkinson’s Disease: Some New Findings - Hu, MD, MPH, PhD, Gang (North American Journal of Medicine and Science, 2009)
Parkinson’s disease (PD) is the second most common neurodegenerative disease of the elderly.1 PD is a debilitating disorder manifested by bradykinesia, resting tremor, muscular rigidity, gait disturbances, and postural reflex impairment.1 The underlying pathologic lesion is the loss of the pigmented neurons of the substantia nigra, and selected brain stem dopaminergic cell groups. However, the causes of PD are not well known. The loss of substantia nigra neurons results in depletion of the neurotransmitter dopamine in these areas. There is evidence that genetic factors play a key role in an early-onset PD.2,3 Studies of twins have provided strong evidence for an important role of environmental factors in the etiology of typical PD.2 The development of PD involves an interaction between genes and environmental factors.2 Thus, its prevention is likely to be at least partly possible. In order to determine interventions that would prevent or delay the onset of PD, modifiable risk factors for the disease have to be identified first. These risk factors could then be used as targets for intervention, and also population-based health education and intervention programs could be developed. Vascular risk factors, such as hypertension, dyslipidemia, and type 2 diabetes, are major risk factors for coronary heart disease (CHD) and maybe also for stroke. In recent years, several prospective studies have assessed the association of vascular risk factors and the risk of PD. In this review, we summarize current results about the role of vascular risk factors in the development of PD risk.